Co-delivery of Salinomycin and Curcumin for Cancer Stem Cell Treatment by Inhibition of Cell Proliferation, Cell Cycle Arrest, and Epithelial–Mesenchymal Transition - Zhao, Yongmei; Wang, Kaikai; Zheng, Yuanlin; Zeng, Xiaobao; Lim, Yi Chieh; Liu, Tianqing (Frontiers in Chemistry, 2021)
Malignant cancer is a devastating disease often associated with a poor clinical prognostic. For decades, modern drug discoveries have attempted to identify potential modulators that can impede tumour growth. Cancer stem cells however are more resistant to therapeutic intervention which often leads to treatment failure and subsequent disease recurrence. Here in this study, we have developed a specific multi-target drug delivery nanoparticle system against breast cancer stem cells (BCSCs). Therapeutic agents, curcumin and salinomycin, have complementary functions of limiting therapeutic resistance and eliciting cellular death, respectively. By conjugation of CD44 cell-surface glycoprotein with the PLGA nanoparticles loaded with curcumin and salinomycin, we investigated the cellular uptake of BCSCs, drug release, therapeutic efficacy against BCSCs. We found this CD44-targeting co-delivery nanoparticles are highly efficacious against BCSCs by inducing G1 cell-cycle arrest and limiting epithelial–mesenchymal transition. This curcumin and salinomycin co-delivery system could be an efficient treatment approach to target malignant cancer without the repercussion of disease recurrence.